Microbial population structure in a stratified, acidic pit lake in the Iberian Pyrite Belt. Issue 7 (1st July 2020) - Grettenberger, Christen L.; Mccauley Rench, Rebecca L.; Gruen, Danielle S.; Mills, Daniel B.; Carney, Colin; Brainard, Jamie; Hamasaki, Hiroshi; Ramirez, Ramses; Watanabe, Yumiko; Amaral-Zettler, Linda A.; Ohmoto, Hiroshi; Macalady, Jennifer L.
Abstract: We examined the geochemistry and bacterial and archaeal community structure in the acidic (pH < 2.4) pit lake at Peña de Hierro, near the headwaters of the Río Tinto. The lake has strong vertical gradients in light, O2, pH, conductivity, and dissolved ions. Bacterial and archaeal communities between 0 and 32 m displayed low species richness and evenness. Relatives of iron cycling taxa accounted for 60-90% of the operational taxonomic units (OTUs) throughout the water column. Relatives of heterotrophic, facultative Fe(III)-reducing species made up more than a third of the bacterial and archaeal community in the photic zone. Taxa related to Fe(II) oxidizers Ferrithrix thermotolerans and Acidithix ferrooxidans were also abundant in the photic zone. Below the photic zone, relatives of the lithoautotrophic Fe(II) oxidizers Leptospirillum ferrooxidans and Ferrovum myxofaciens bloomed at different depths within or just below the oxycline. Thermoplasmatales predominated in the deep, microoxic zone of the lake. The microbial population structure of the lake appears to be influenced by the production of oxygen and organic matter by phototrophs in a narrow zone at the lake surface and by strong geochemical gradients present in the water column that create distinct niches for separate Fe(II) oxidizers.